(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This Prospective study was conducted to do profiling and analysis of Medico-legal cases attending the JSS Medical College and Hospital, Mysuru for a period of two years. Total 2033 Medical-legal cases which were registered during the time period were analysed. Analysing the pattern of such unnatural events, would provide a vital data for healthcare professionals, civil administrators, investigating agencies of state and judiciary to devise and implement appropriate and adequate strategies so as to reduce such incidences from happening. Majority of the cases were RTA, followed by poisoning. Among all the admitted cases, majority of the cases recovered and discharged. The mortality rate is low among the admitted cases, only 9.9% of cases were hospital deaths. Most of the cases occurred during the time period of 12.01pm to 6pm followed by 6.01pm to 12am. The age group of 21-30 years are the most frequently affected. Majority of the victims were males. Suicide by hanging is more frequent among females compared to males, despite of predominant male population among the MLCs.